Scrutinizing EFL Learners’ English Pronunciation Oversight: A Consonant Error Analysis - Ida Parida; Muhammad Danial; Dwi Adi Nugroho; Pipit Muliyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Pronunciation is a substantial aspect of communicative competence in English as a Foreign Language (EFL), though systematic phonetic errors frequently disrupt understandability. The research aims to identify the types and reasons for English consonant pronunciation errors made by Indonesian EFL learners at the university level. Using a quantitative-descriptive design within an Error Analysis framework, the study investigated an oral corpus comprising 3,920 words collected from 10 pre-service English teachers through reading tasks and semi-structured interviews. Results show that substitution constitutes the most common error strategy (68%) and particularly for phonemes not present in learners' native phonetic inventory, namely dental fricatives (/ð/, /θ/) and voiced labiodental fricative (/v/). In addition, omission errors (27%) were common in the word-final consonant part, reflecting phonetic constraints and a preference for syllabic simplification, while insertion errors were rare (5%). These results underscore the role of language interference and articulatory markedness, demonstrating a paradox in achievement whereby successful attainment of general language skills does not guarantee phonological allegiance. In the context of pedagogy, this has implications for EFL curricula, specifically the incorporation of explicit phonetic awareness instruction by structuring focused articulatory interventions into syllabi to minimize systematic pronunciation errors effectively.